Characteristics of first-time varenicline users - A cross-sectional study in Finnish quitters - Hanna E. Tervonen; Juha H. O. Turunen; Christine L. Baker; Juha Laine; Kari Linden (BMC, 2017)
Abstract Background Varenicline is an efficacious medicine for smoking cessation (SC) but little is known about the characteristics of varenicline users. This study examined the characteristics of first-time (naïve) varenicline users in Finland and compared those who had previously used SC pharmacotherapy to those who were trying SC pharmacotherapy for the first time. Methods A cross-sectional survey was conducted in Finnish community pharmacies between February 2014 and January 2015. Pharmacy customers purchasing a varenicline starter package for the first time ever were asked to complete a questionnaire or to participate in a structured interview conducted by the pharmacist (identical questions). The questionnaire included questions about demographic characteristics, smoking habits, previous cessation attempts and factors associated with varenicline use. Results Altogether 98 people completed the survey. The majority were daily smokers (96%, n = 94), with a history of over 10 years of regular smoking (94%, n = 92), and a strong/very strong nicotine dependence (67%, n = 66). Half of the participants (54%, n = 53) were trying a SC pharmacotherapy for the first time. Demographic characteristics and smoking habits were similar between first-time and previous users of SC medications (p > 0.05). Health centers (42%, n = 41) and occupational health care clinics (37%, n = 36) were the most common sources of varenicline prescriptions. The majority of participants received the prescription for varenicline after mentioning their desire for quitting to a physician (70%, n = 69). Conclusions Considering the relatively large proportion of SC naïve medicine users among new users of varenicline, smokers who have previously been reluctant to quit smoking, to use other pharmacological SC interventions, or perhaps unaware of these options may be interested in attempting cessation with varenicline. Most participants made the initiative to discuss their smoking with the physician, which led to varenicline prescribing. This suggests that physicians may not satisfactorily recognize their patients' nicotine dependence and desire to quit, and they should more actively support patients' smoking cessation.